2018
DOI: 10.1200/po.17.00019
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling of T-Cell Neoplasms Reveals Frequent JAK1 and JAK3 Mutations With Clonal Evasion From Targeted Therapies

Abstract: These results underscore the utility of profiling occurrences of resistance to standard regimens and support JAK enzymes as rational therapeutic targets for T-cell leukemias and lymphomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 53 publications
(48 reference statements)
1
26
0
Order By: Relevance
“…Germline controls were sequenced in 53 cases (19.3%). The number of analyzed patients varied from 3 to 71 patients across the 10 studies [9][10][11][12][13][14][15][16][17][18]. After subtracting all cases reported in more than one study, we identified 275 unique T-PLL cases as the core cohort.…”
Section: Characteristics and Overlaps Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Germline controls were sequenced in 53 cases (19.3%). The number of analyzed patients varied from 3 to 71 patients across the 10 studies [9][10][11][12][13][14][15][16][17][18]. After subtracting all cases reported in more than one study, we identified 275 unique T-PLL cases as the core cohort.…”
Section: Characteristics and Overlaps Of Included Studiesmentioning
confidence: 99%
“…[14][15][16][17][18][19][20], JAK3 (Ex. [11][12][13][14][15][16][17][18][19], and/or STAT5B (Ex. [15][16][17], was included.…”
Section: Characteristics and Overlaps Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations